Survivance, sovereignty, and story: teaching American Indian rhetorics - King, Lisa, author; Gubele, Rose, author; Anderson, Joyce Rain, author; Utah State University Press, publisher (Colorado State University. Libraries, 2015)
Focusing on the importance of discussions of sovereignty and of the diversity of American Indian communities, Survivance, Sovereignty, and Story offers a variety of ways to teach and write about Indigenous North American rhetorics. These essays introduce Indigenous rhetorics as they frame both how and why they would be taught in an American university writing classroom.--Provided by publisher.
Waking in the dark / Janice Gould -- Foreword: Alliances and community building: teaching Indigenous rhetorics and rhetorical practices / Resa Crane Bizzaro -- Introduction: Careful with the stories we tell: naming "survivance," "sovereignty," and "story" -- Sovereignty, rhetorical sovereignty, and representation: keywords for teaching Indigenous texts / Lisa King -- Socioacupuncture pedagogy: troubling containment and erasure of indigeneity in the composition classroom / Sundy Wantanabe -- Decolonial skillshare: Indigenous rhetorics as radical practice / Qwo-li Driskill -- Performing Nahua rhetorics for civic engagement / Gabriela Raquel Røos -- Un-learning the "pictures in our heads": teaching the Cherokee Phoenix, Boudinot, and Cherokee history / Rose Gubele -- Heartspeak from the spirit: songs of John Trudell, Keith Secola, and Robbie Robertson / Kimberli Lee -- Making Native space for graduate students: a story of collective Indigenous rhetorical practice / Andrea Riley-Mukavetz and Malea D. Powell -- Remapping colonial territories: bringing local Native knowledge into the classroom / Joyce Rain Anderson -- Rhetorical sovereignty in written poetry: survivance through code switching and translation in Laura Tohe's Tsøyi'/Deep in the rock: reflections on Canyon de Chelly / Jessica Safran Hoover -- Toward a decolonial digital and visual American Indian rhetorics pedagogy / Angela Haas -- Holy wind / Janice Gould -- The story that follows: an epilogue in three parts / Lisa King, Rose Gubele, and Joyce Rain Anderson.
Keywords: Indians of North America -- Study and teaching (Higher); Rhetoric -- Study and teaching (Higher) -- United States; Sovereignty -- Study and teaching (Higher) United States; Cultural pluralism -- Study and teaching (Higher) -- United States; Survival -- Study and teaching (Higher) -- United States; Government, Resistance to -- Study and teaching (Higher) -- United States